GEMTraits: A database and R package for accessing and analyzing plant functional traits from the Global Ecosystems Monitoring Network - Shenkin, A; Bentley, L; Asner, G; Diaz, S; Enquist, B; Malhi, Y; Girardin, C (University of Oxford, 2017)
This dataset contains a POSTGRESQL database with demographic and functional trait data on trees from 10 1-hectare permanent plots across an elevation transect from 3500m to 200m in SE Peru. They comprise part of the Global Ecosystems Monitoring Network (GEM; http://gem.tropicalforests.ox.ac.uk) and are operated by the Andes Biodiversity Ecosystems Research Group (ABERG, http://www.andesconservation.org). Further site details are described by Malhi (2017, in prep). Functional trait data includes leaf chemistry, leaf morphology, leaf venation, branch architecture, and 3D crown architecture measurements. Both sun and shade leaves were sampled where available. Microenvironmental data includes vertical light profiles from crown top to forest floor in a subset of trees, light availability at each measured branch, and the location of sampled branches within crowns. An R package ("gemtraits") for data access and analysis is also provided. AS and LPB contributed equally to the database construction. Although this data is under embargo, any parties that wish to request access to it should contact the depositor (Dr Alexander Shenkin, Environmental Change Institute, Oxford University Centre for the Environment).